Advanced Oil Crop Biorefineries. - Kazmi, Abbas; Clark, James H.; Kraus, George A.; Stamatelatou, Katerina; Mulder, Wim (Royal Society of Chemistry, The Ingram Publisher Services [distributor], 2011)
Annotation In Europe the main oil-rich crops are sunflower, rapeseed and olive which are grown primarily for food. This book discusses how to convert this whole crop into energy, food and bioproducts.
Keywords: Oilseed plants.; Biomass energy.; Energy crops.; elektronické knihy; electronic books